2021
DOI: 10.1158/1078-0432.ccr-20-2096
|View full text |Cite
|
Sign up to set email alerts
|

MRI and 18FET-PET Predict Survival Benefit from Bevacizumab Plus Radiotherapy in Patients with Isocitrate Dehydrogenase Wild-type Glioblastoma: Results from the Randomized ARTE Trial

Abstract: PURPOSE: To explore a prognostic or predictive role of magnetic resonance imaging (MRI) and O-(2-18 F-fluoroethyl)-L-tyrosine ( 18 FET) positron emission tomography (PET) parameters for outcome in the randomized multi-center trial ARTE that compared bevacizumab plus radiotherapy with radiotherpay alone in elderly patients with glioblastoma. EXPERIMENTAL DESIGN: Patients with isocitrate dehydrogenase wild-type glioblastoma aged 65 years or older were included in this post-hoc analysis. Tumor volumetric and appa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 50 publications
0
15
1
Order By: Relevance
“…MRI is indispensable in neuro-oncology practice, yet quantitative, standardized, and robust MRI-based biomarkers are currently sparse ( 16 ). Recent clinical studies demonstrated the potential of MRI in predicting the response to antiangiogenic treatment in pediatric and adult brain tumors ( 48 , 49 ). Quantitative characterization of vascular properties is a common MRI application in the imaging of brain tumors, due to the ability of gadolinium-based contrast agents to penetrate and enhance those tumor regions with a disrupted BBB ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…MRI is indispensable in neuro-oncology practice, yet quantitative, standardized, and robust MRI-based biomarkers are currently sparse ( 16 ). Recent clinical studies demonstrated the potential of MRI in predicting the response to antiangiogenic treatment in pediatric and adult brain tumors ( 48 , 49 ). Quantitative characterization of vascular properties is a common MRI application in the imaging of brain tumors, due to the ability of gadolinium-based contrast agents to penetrate and enhance those tumor regions with a disrupted BBB ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…AA PET has been reported as a potentially viable adjunct in analyzing pseudoresponse. As a prognostication tool in the context of pseudoresponse, AA PET shows promise with existing evidence showing that persistent 18 FET-PET signal on NCE tumor during bevacizumab treatment is predictive of a significant decrease in OS ( Wirsching et al, 2021 ).…”
Section: Imaging To Assess For Pseudoresponse Following Immunotherapymentioning
confidence: 99%
“…The prognostic performance of perfusion MRI parameters (DSC and DCE) and ADC values has been documented in patients with newly diagnosed and recurrent glioblastomas. [24][25][26][27][28] As a prognostic factor from different viewpoints, Schob et al reported that ADC histogram parameters were strongly correlated with the expression of the proliferation marker, Ki-67, and total nuclear area of MB. 29 However, for both PA and MB, the presence or absence of correlations between these MRI parameters and survival prognosis is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Another important role of MRI is its prognostication. The prognostic performance of perfusion MRI parameters (DSC and DCE) and ADC values has been documented in patients with newly diagnosed and recurrent glioblastomas 24–28 . As a prognostic factor from different viewpoints, Schob et al.…”
Section: Introductionmentioning
confidence: 99%